Right-wing populism and gender: European perspectives and beyond - Dietze, Gabriele; Roth, Julia (Gender studies, 2020)
Frontmatter -- Contents -- Right-Wing Populism and Gender: A Preliminary Cartography of an Emergent Field of Research -- Authoritarian Right-Wing Populism as Masculinist Identity Politics. The Role of Affects -- Why Gender and Sexuality are both Trivial and Pivotal in Populist Radical Right Politics -- Sexual Politics from the Right. Attacks on Gender, Sexual Diversity, and Sex Education -- Post-Socialist Conditions and the Orbán Government’s Gender Politics between 2010 and 2019 in Hungary -- Man, Woman, Family. Gender and the Limited Modernization of Right-Wing Extremism in Austria -- Sexual Politics as a Tool to “Un-Demonize” Right-Wing Discourses in France -- Identitarian Gays and Threatening Queers, Or: How the Far Right Constructs New Chains of Equivalence -- Why Are Women Attracted to Right-Wing Populism? Sexual Exceptionalism, Emancipation Fatigue, and New Maternalism -- Populist Mobilizations in Re-Traditionalized Society: Anti-Gender Campaigning in Slovenia -- ‘You’re Fired!’ Retrotopian Desire and Right-Wing Class Politics -- The Alternative Right, Masculinities, and Ordinary Affect -- Angry Women: Poland’s Black Protests as ‘Populist Feminism’ -- Intersectionality Strikes Back: Right-Wing Patterns of En-Gendering and Feminist Contestations in the Americas -- Acknowledgements -- List of image sources -- Authors